Making compost by using bio catalyst to household organic waste of the Village - Yovan Witanto; Hendra; Indra Adi Saputra (Dharmakayana, 2024)
By request of the residents of the Neighborhood-30 in the Urban-village Sawah Lebar Baru Bengkulu City, making compost to household organic waste by using the EM4 bio activator was completed. Employing small volume what so called composter bag, the waste was collected in the bag after one pile the bio activator was poured over and so after another. This technique makes a composting time reduced. This transfer of knowledge to the residents about making compost and the benefit of compost made them motivated to manage household waste separately since their houses.